Curing kinetics of a furan resin and its nanocomposites - Rivero, Guadalupe (2011)
A furan resin was synthesized from furfural and phenol and it was expected to have similar properties to the commonly used phenolic resins because the former was obtained by the replacement of formaldehyde by furfural, reducing the dangerous formaldehyde emissions. In the present work, nanocomposites were obtained by the in situ addition of 2% of different types of clays to the furan resin to enhance the polymer performance. Montmorillonite natural clay Cloisite® Na+ and the chemically modified ones, Cloisite® 30B and Cloisite® 10A were used. A clay dispersion comparison among the nanocomposites was performed. The curing kinetics of the furan resin and its composites was characterized by Differential Scanning Calorimetry. Free kinetic models were applied in order to obtain and compare the activation energy of each process. Vyazovkin numerical analysis was found to provide the most accurate method to analyze the variation of the activation energy (E) with the reaction conversion. Some differences arise in the activation energy vs. conversion profile among the materials studied. These differences were related to the variations in the viscosity and the chemical groups with the evolution of the curing reaction, followed by infrared spectroscopy. The nanocomposites containing the organically modified clays showed an additional peak in the last stage of the curing process due to parallel reactions including the beginning of the organic modifier decomposition.